The Value of Children's Education in the Katoba Ritual and its Implications for Moral Education - Al Kahar, Aris Armeth Daud; Bogatyreva, Svetlana Nikolaevna; Dewanti, Sintha Sih; Arif, Mahmud; Abroto, Abroto (Journal of Elementary Educational Research, 2025)
In the context of Muna society, katoba exists as an educational ritual that continues to survive and exist amidst the onslaught of modernization. This study aims to examine how children are educated in the katoba ritual and its implications for moral education. This study uses Spradley's qualitative approach, which is included in the type of ethnographic research. This approach emphasizes an in-depth study of a particular cultural group or community. Data collection was conducted through observation, interviews, and documentation. Data collection was conducted through observation, interviews, and documentation. The data sources were one traditional leader (LS) and one religious leader (LM) who performed the katoba ritual. The research location in this paper is in the South Wakorumba district, Muna Regency. The selection of South Wakorumba district as the research location is based on the fact that South Wakorumba sub-district still maintains authentic Muna culture, thus the implementation of the katoba ritual is still carried out continuously. The results of the study indicate that the katoba ritual has a moral educational meaning contained in each of its three main steps: the initial implementation, the main implementation, and the closing implementation. The initial stage is marked by the wearing of traditional Muna clothing, the main stage is the core procession, namely the giving of toba advice from the priest to the toba participants, and the third is the banquet, which is the final procession in the katoba ritual.This educational value is obtained from the advice expressed by the imam to the Toba participants. The educational values ​​are morals towards Allah, morals towards others and morals towards the environment.